Impact of Government Fiscal Space and Manpower to The Gross Domestic Products of Indonesia Period 1990-2015 - Enjarwati, Tria; Djoko Mursinto (Universitas Airlangga, 2018)
To purpose of this study was to examine and analyze the effect of fiscal space and labour absorption to Indonesia Gross Domestic Product (GDP) within period 1990-2015. This study uses the least squares method or Ordinary Least Square (OLS) with time series data. Variables used in this study is the Gross Domestic Product (GDP) as the dependent variable, whereas for independent variables using the fiscal space and labour absorption. The results of regression calculations using the least squares method or Ordinary Least Square (OLS) in this study indicate that the fiscal space variable has a positive significant effect, and labour absorption variable has a positive significant effect to indonesia Gross Domestic Product (GDP). Keywords: Gross Domestic Product (GDP), Fiscal Space and Labor Absorption, Ordinary Least Square (OLS)